Conventional Versus Prolonged Infusion of Meropenem in Neonates With Gram-negative Late-onset Sepsis: A Randomized Controlled Trial. Issue 4 (April 2017) - Shabaan, Abd Elazeez; Nour, Islam; Elsayed Eldegla, Heba; Nasef, Nehad; Shouman, Basma; Abdel-Hady, Hesham
Abstract : Background: Gram-negative bacteria are associated with significant morbidity and mortality in preterm and term newborns. Meropenem has widespread efficacy and often allows for monotherapy in this group. Prolonged infusion instead of infusion over 30 minutes has been suggested to result in higher microbiologic efficacy. Objective: To compare the clinical and microbiologic efficacy and safety of prolonged infusions versus conventional dosing of meropenem in neonates with Gram-negative late-onset sepsis (GN-LOS). Methods: A prospective, randomized clinical trial was conducted in neonates with GN-LOS admitted to neonatal intensive care unit (NICU), Mansoura University Children's Hospital, between August 2013 and June 2015. Patients were randomly assigned to receive either intravenous infusion of meropenem over 4 hours (infusion group) or 30 minutes (conventional group) at a dosing regimen of 20 mg/kg/dose every 8 hours and 40 mg/kg/dose every 8 hours in meningitis and Pseudomonas infection. Clinical and microbiologic success in eradication of infection were the primary outcomes. Neonatal mortality, meropenem-related (MR) duration of mechanical ventilation, MR length of NICU stay, total length of NICU stay, duration of respiratory support (RS), duration of mechanical ventilation, MR duration of inotropes and adverse effects were secondary outcomes. Results: A total of 102 infants (51 in each group) were recruited. The infusion group demonstrated a significantly higher rate of clinical improvement and microbiologic eradication 7 days after starting meropenem therapy compared with the conventional group. Mortality and duration of RS were significantly less in the infusion group compared with conventional group. Acute kidney injury after meropenem treatment was significantly less in the infusion group compared with the conventional group. Conclusions: Prolonged infusion of meropenem in neonates with GN-LOS is associated with higher clinical improvement, microbiologic eradication, less neonatal mortality, shorter duration of RS and less acute kidney injury compared with the conventional strategy.